Notes on liberal (arts) education discourse - Kontowski, Daniel (Kultura-Społeczeństwo-Edukacja, 2019)
The following essay discusses liberal (arts) education from critical discourse analysis perspective. After a historical and philosophical introduction, three examples of liberal education discourse are discussed: 1) ‘liberal arts’ vs. ‘liberal education’, 2) ‘liberal arts’ and ‘neoliberal arts’ and 3) descriptions of liberal education at Wagner College in 1970 and 2013. The article concludes with a general reflection on liberal education in the current educational landscape and a tentative agenda for using the critical discourse analysis toolbox in further studies.